An efficient target–intermediate recycling amplification strategy for ultrasensitive fluorescence assay of intracellular lead ions. Issue 54 (20th June 2017) - Wen, Zhi-Bin; Liang, Wen-Bin; Zhuo, Ying; Xiong, Cheng-Yi; Zheng, Ying-Ning; Yuan, Ruo; Chai, Ya-Qin
Abstract : An ultrasensitive fluorescence assay for intracellular Pb 2+ determination was proposed through target–intermediate recycling amplification based on metal-assisted DNAzyme catalysis and strand displacement reactions. Abstract : An ultrasensitive fluorescence assay for intracellular Pb 2+ determination was proposed through target–intermediate recycling amplification based on metal-assisted DNAzyme catalysis and strand displacement reactions. Compared with only target recycling-based fluorescence assay with an M amplification ratio, the proposed assay could achieve an M × N amplification ratio to obtain an improved sensitivity by more than 10 times, in which M and N are the amplification ratios of target recycling and intermediate recycling, respectively. Remarkably, this proposed ultrasensitive fluorescence assay could be applied to the determination of various analytes with the well-designed detection probe, especially in intracellular assay, providing a promising tool for clinical diagnosis and biomedical detection.